Peer settings induce cheating on task performance - Agnes Bäker; Mario Mechtel (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2015)
Recent research has shown that the presence of peers can increase individual output both in the lab and the field. This paper tests for negative side effects of peer settings. We investigate whether peer settings are particularly prone to cheating even if they do not provide additional monetary benefits of cheating. Participants in our real effort experiment had the opportunity to cheat when declaring their output levels. Although cheating did not have different monetary consequences when working alone than when working in the presence of a peer, we find that cheating is a more severe problem in peer settings.
Keywords: J20; J30; M50; 330; cheating; peer effects; organizational design; personnel economics; experimental economics